450 MHz for Smart Metering & Smart Grid - Elhaddad, Ahmed; Irnstorfer, Florian; Fischer, Georg (21. ITG/GMA Fachtagung Sensoren und Messsysteme 2022, 2022)
450 MHz for Smart Metering & Smart Grid<br
Keywords: Cellular IoT; 450 MHz; Smart Grid; Smart Metering; Antenna Detuning; PAE

Energy Consumption Evaluation of Cellular Narrowband Internet of Things (NB-IoT) Modules - Elhaddad, Ahmed; Bruckmeyer, Heiko; Hertlein, Markus; Fischer, Georg (2020 IEEE 6th World Forum on Internet of Things (WF-IoT), 2020)
Communications field is witnessing an abrupt growth in the number of connected devices. The connected devices do not only include smartphones, but also connected devices through Internet of Things (IoT). Therefore, 3GPP defined Narrowband Internet of Things (NB-IoT) standard in LTE Rel-13 in order to serve low data rate IoT applications over mobile networks. NB-IoT modules are expected to have a low energy consumption in order to allow for battery usage of more than 10 years and provide a wide coverage area. At our institute, we developed a lab system setup in order to characterize the energy consumption of 3 NB-IoT modules from 3 different manufacturers using an LTE network mockup model. Accordingly, we measured the energy consumption by the modules during different phases of communication, and derived a data traffic dependent energy consumption model in order to estimate the corresponding expected battery lifetime. Furthermore, we measured the energy consumption per bit of the modules against the different number of uplink Narrowband Physical Uplink Shared Channel (NPUSCH) repetitions.
unpublished
Keywords: 5G; mMTC; LPWAN; CIoT; NB-IoT; Energy consumption; Battery lifetime

Energy Saving of Narrowband Internet of Things (NB-IoT) Applications using Release Assistance Indication (RAI) Feature in Rel. 13 - Elhaddad, Ahmed; Irnstorfer, Florian; Duemler, Burkhard; Fischer, Georg (embedded world Conference 2022, 2022)

Integration of Cellular Internet of Things Modules into Sport Wearable - Elhaddad, Ahmed; Irnstorfer, Florian; Duemler, Burkhard; Fischer, Georg (European Technology Platform on Smart Systems Integration (EPoSS), 2021)
Narrowband Internet of Things (NB-IoT) and LTE for Machine Type Communications (LTE-M) are gaining more momentum as Cellular Internet of Things (CIoT) technologies, which provide cellular connectivity for IoT applications. Thus, mobile operators can support IoT applications by exploiting the existing network infrastructure. These standards are designed to provide large coverage area, low energy consumption devices and low cost devices. In our project, we are integrating sensors, NB-IoT and LTE-M modules into smart wearables namely: a NB-IoT module into a Smart Shoe and a NB-IoT/LTE-M module into a Smart Jacket. Therefore, sensor data are transmitted to a cloud platform directly without using a smartphone as a hub node (“phoneless” solution). This will allow for health monitoring of athletes during activities and during their recovery phase in case of rehabilitation and injury prevention. <

PMSE-xG –Wireless Communication in Mobile Networks for Programme Making and Special Events - Hertlein, Markus; Bühlmeyer, Jonas; Elhaddad, Ahmed; Fischer, Georg (2nd International Conference on Signals and Systems 2018 (ICSigSys 2018), 2018)
This paper provides a short overview of the German research and development (R&D) project PMSE-xG, which aims to create the prerequisites for using the next mobile standard for broad-band low-latency ultra-reliable connections (5G) especially for Programme Making and Special Events (PMSE). The PMSE manufacturers have so far focused on highly specialized, link-based solutions. This strategy was undermined by the fact that more and more spectrum is assigned to mobile communication systems like Long Term Evolution (LTE). Therefore, both technologies are competing for the rare spectrum. Working with the current standard for wireless communication Long Term Evolution (LTE), the PMSE-xG project is a first feasibility study to integrate PMSE applications into a mobile communication standard and aims to integrate these different use cases of PMSE through future projects into 5G. Through the interaction and cooperation with different stakeholders from industry, research, standardization, regulation and users, PMSE-xG tries to achieve this. Furthermore, it will lay the foundations for other vertical industries in 5G and for further cooperation with them. Furthermore, the video demonstrator is introduced in this paper. Still some work has to be done but the goals of the project are reachabl
Keywords: PMSE; SDR; LTE; 5G; low-latency; broad-band; ultra-reliable wireless communication

Protocol Stack Optimization With Cellular IoT Applications - Irnstorfer, Florian; Elhaddad, Ahmed; Dümler, Burkhard; Fischer, Georg (embedded world Conference 2022, 2022)